Two For One : How Leveraging Small Claims Procedures Can Improve Judicial Efficiency and Access to Justice - Petkova, Svetozara; Senderayi, Runyararo Gladys (World Bank, Washington, DC, 2020)
People often argue about little things in both their personal and their business relationships. From a legal perspective, low-value monetary disputes are known as small claims. The monetary threshold for a claim to be qualified as “small” is generally determined by the economic conditions of a country, but it can also reflect a policy choice to subject a subset of the overall demand for court services to specific procedural rules. Given the frequency of small claims if they are not resolved quickly and efficiently, they can inundate the justice system, drain limited judicial resources, and generate case backlogs, while ruining personal relationships and frustrating business operations. Conversely, some small claims cases do not even get to have their day in court because litigation is too costly for many ordinary citizens. This means that access to justice is hindered. Therefore, unresolved small claims can exacerbate inefficiency in court processes and contribute to a lack of access to justice. Societies cannot afford to let a growing body of minor disputes clog justice systems, stall economic activity, and fuel social tensions. Thus, an increasing number of countries are designing special rules for such disputes; these are often known as small claims, simplified, or fast-track procedures. Currently, as many as 132 economies have either a stand-alone small claims court or a simplified procedure for small claims.